Revealing the Weak Interaction Mechanism of Crystalline Cellulose Iα by Molecular Dynamics Simulations (Journal of Fiber Bioengineering and Informatics, 2019)
According to our previous works on cellulose Iβ and Iα, the weak interactions, though easily ignored,play certain role in the stability mechanism of nature cellulose. These weak interactions should never beignored or underestimated. In this work, a molecular dynamics study of cellulose Iα was reportedto evaluate the weak interactions under various temperatures. The polar and non-polar solvationinteractions and hydrogen bonding were taken into account. The Van der Waals, electrostatic, polarsolvation and non-polar solvation energy per chain were estimated up to −131.68, −56.38, 29.16 and−41.76 Kcal/mol at room temperature. The weak interactions behaviors of cellulose Iα, including that ofthe cellulose Iβ and Iα reported previously, were compared. The results indicate that hydrogen bondingcontribute obviously for the intrachain stability. The interchain electrostatic interaction maintain areasonable level under 300 K but decreases rapidly with the ascending of temperature. The polar andnon-polar solvation interaction plays an important role not only to interchain under high temperaturebut also to the intersheet stability. In addition, the hydrogen bonding in intersheet is weaker than thatof intrachain and interchain. The result is same as cellulose Iβ that relatively weak hydrogen bondingand strong nonbonded interactions keep the intersheet stability collaboratively.
Keywords: Weak Interaction; Cellulose Iα; Molecular Dynamics; Hydrogen Bonding